An Efficient Synthesis of Alkyl Dithiocarbamates through Michael‐type Addition of Tetraalkylthiuram Disulfides to Electrophilic Alkenes. Issue 10 (26th August 2021) - Hao, Shuai; Ding, Songshuang; Wu, Zhiyong; Bi, Haoyang; Bai, Feng; Yang, Xinling; Wang, Longfei; Wang, Yiying; Shen, Hongtao; Zhao, Mingqin
Abstract: A novel and efficient process for the synthesis of alkyl dithiocarbamates from electrophilic alkenes and tetraalkylthiuram disulfides was presented. The reactions proceed under mild conditions to afford the products in high yields, excellent functional group tolerance and step efficiency. This protocol realizes a pretty interesting methodology for alkyl dithiocarbamates synthesis under a Michael‐type addition progress. Abstract : A facile protocol for the synthesis of alkyl dithiocarbamates from electrophilic alkenes and tetraalkylthiuram disulfides has been achieved. The method proceeds smoothly under mild conditions without any metal catalysts and has a broad range of functional group tolerance.